TWENTY YEARS OF POST-SOVIET RUSSIAN POLITICS: IDEOLOGY AND STATE SYSTEM AND GLOBAL STRATEGY (Сравнительная политика)
Twenty years of post-Soviet Russian politics: ideology and state system and global strategy.